The Importance of Rhodoliths Bearing Beds in Paleoenvironmental Analysis of (the Middle Miocene) Benghazi Formation, NE Libya. - Muftah, Ahmad M.; Sowan , Abdulbadi M.; Al-Amary , Abdulrahim S.; Al-Warfalli , Muntasir F. (Libyan Journal of Science &Technology, 2025)
Abstract: Two Rhodoliths bearing beds have been recognized in the Middle Miocene rocks of the Benghazi Formation at Al Jabal al Akhdar in Northeastern Libya. Three sections, the Daryanah-Abyar (DA) road cut and the Farkash Quarry in the vicinity of Daryanah village, and Majdoub Lake east of Benghazi city have been sampled and studied based on the faunal and floral (algal) evidences with integration of lithofacis characteristic in order to evaluate the environmental setting of Benghazi Formation at these locations. The repetition of Rhodoliths bearing beds is recognized twice in the Daryanah –Abyar (DA) road cut section and Farkash Quarry (FQ) section, whereas only once in Majdoub Lake section. The established Miocene units are spreadout in the range of ramp paleoenvironmental model. A lithological correlation has been built in to trace the lateral extension of the rhodoliths bearing-beds. The presence of the nodular rhodoliths below FWWB (i.e. >50 m water depth) indicates a proximal part of the middle ramp. Based on presence of Borelis melo and Miogypsinids the Benghazi Formation is dated as Miocene.